The Persistence of Financial Distress - Athreya, Kartik; Mustre-del-Río, José; Sánchez, Juan M. (Review of Financial Studies, 2019)
[Using proprietary panel data, we show that many U.S. consumers experience financial distress (35% when distress is defined by having debt in severe delinquency, e.g.) at some point in their lives. However, most distress events are concentrated on a much smaller proportion of consumers in persistent trouble: fewer than 10% of borrowers account for half of all distress events. These facts can be largely accounted for in a straightforward extension of a workhorse model of unsecured debt with informal default that accommodates a simple form of heterogeneity in time preference.]